Factores socioeducativos y sentido de coherencia asociados a la calidad de vida en adolescentes de Lima Metropolitana - Dejo-Vásquez, Mariela (2018)
The research aimed to explain the construct Quality of Life associated with socio-educational factors and the sense of coherence in adolescents of Lima Metropolitan area. The study population consisted of 1211 adolescents aged 12 to 19 attending public and private educational institutions of Lima Metropolitan area. Data was obtained through the Questionnaire for Assessing Adolescent Students’ Quality of Life (CCVA), the Sense of Coherence Scale (SCS), and a questionnaire on the study variables Family Context, School Climate, and Risk Factors. The results show that the three dimensions of the sense of coherence are good predictors of quality of life. The socio-educational factors Family Context and School Climate presented statistically significant differences in quality of life levels depending on the socio-economic sectors.